Hubungan Status Nutrisi Saat Masuk Rumah Sakit dengan Outcome pada Pasien Stroke Iskemik. - Aditya Purnama Meidarahman; Fakhrurrazy Fakhrurrazy; Triawanti Triawanti (Homeostasis, 2019)
Abstract: Determination of nutritional status in ischemic stroke patients is very important because the condition of malnutrition is one of the risk factors that can affect outcomes in ischemic stroke patients. The purpose of this study was to determine the relationship of nutritional status at hospital admission to outcome in ischemic stroke patients. This study was an observational analytic study conducted in a cross sectional manner. Samples were selected based on inclusion criteria and also exclusion through history taking and viewing the patient's medical records so that 37 samples were obtained. assessment of nutritional status using a Mini Nutritional Assessment (MNA) after that a week later the patient will be examined for outcome values using a modified Rankin Scale (mRS). The analysis of results is carried out using the spearmans rho correlation test. The results of this study obtained a p= 0.00 and the value of r= -0.704. In conclusion, there is a relationship between the nutritional status of patients at the time of hospital admission and outcome in ischemic stroke patients in the Ulin Hospital Banjarmasin. Keywords: ischemic stroke, mini nutritional assessment (MNA), outcome Abstrak: Penentuan status nutrisi pada pasien stroke iskemik sangat penting untuk dilakukan karena kondisi malnutrisi merupakan salah satu faktor risiko yang dapat mempengaruhi outcome pada pasien stroke iskemik. Tujuan penelitian ini adalah untuk mengetahui hubungan status nutrisi saat masuk rumah sakit dengan outcome pada pasien stroke iskemik. Penelitian ini bersifat observasional analitik yang dilakukan secara cross sectional. Sampel dipilih berdasarkan kriteria inklusi dan juga ekslusi melalui anamnesis serta melihat rekam medik pasien pada 37 sampel. Penilaian status nutrisi menggunakan Mini Nutritional Assessment (MNA) dan setelah seminggu kemudian pasien akan diperiksa nilai outcome menggunakan modified Rankin Scale (mRS). Data dianalisis dengan menggunakan uji korelasi spearman’s rho. Hasil dari penelitian didapatkan nilai p=0,00 serta nilai r= -0,704. Kesimpulannya terdapat hubungan antara status nutrisi pasien saat pertama kali masuk rumah sakit dengan outcome pada pasien stroke iskemik di RSUD ulin Banjarmasin. Kata-kata Kunci: Stroke Iskemik, mini nutritional assessment (MNA), outcome